Shallow Convection and Precipitation Over the Southern Ocean: A Case Study During the CAPRICORN 2016 Field Campaign. Issue 9 (29th April 2021) - Lang, F.; Huang, Y.; Protat, A.; Truong, S. C. H.; Siems, S. T.; Manton, M. J.
Abstract: Marine boundary layer clouds and precipitation observed in a sustained period of open mesoscale cellular convection (MCC) over the Southern Ocean (SO) are investigated using Clouds, Aerosols, Precipitation, Radiation, and atmospherIc Composition Over the southeRn oceaN 2016 observations, Himawari‐8 products, and numerical simulations. The shallow convection was characterized by the presence of supercooled liquid water and mixed‐phase clouds in the sub‐freezing temperature range, consistent with earlier in‐situ observations where ice multiplication is found to be active in producing large quantities of ice in open MCC clouds. Ice‐phase precipitation was observed to melt below cloud base with evidence of cold pools produced in a decoupled boundary layer. Convection‐permitting simulations using the weather research and forecasting model were able to reproduce many of the surface meteorological features and their evolution. However, the evolution of the boundary layer height and the degree of decoupling were poorly simulated, along with the absence of cold pools. The observed cloud morphology and microphysical characteristics were also not well reproduced in the control simulation with the Thompson microphysics scheme, where too much supercooled water was simulated in a too homogenous cloud field. Sensitivity experiments with modified microphysical parameters led to a higher production of glaciated clouds and precipitation. Sensitivity experiments with different boundary layer schemes and vertical resolution, however, showed a smaller impact. A bias of ∼4°C in the initial boundary conditions of the sea surface temperature is discussed. This study highlights the challenge of representing the complex physical processes that underpin the cloud, precipitation, and boundary layer characteristics of the open MCC over the SO. Key Points: Observations under open mesoscale cellular convection over the Southern Ocean are characterized by precipitation followed by cold pools Ice multiplication processes were likely to be active in the open mesoscale cellular convection clouds Weather research and forecasting simulations show only weak decoupling of the boundary layer, which might be associated with an sea surface temperature bias in the initial boundary conditions